2022
DOI: 10.1021/acsanm.2c01286
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Coupling Effects Enhance the Performance of Ionic-Polymer-Gated Graphene Photodetectors

Abstract: Interface coupling of graphene/semiconductor heterostructures has been studied extensively for applications such as photodiodes, solar cells, and photodetectors as the demand for efficiency and performance increases. Here, a method is proposed to enhance the photogain of graphene/silicon photodetectors. The method is to manipulate the interface coupling of graphene/silicon by optimizing the voltage of ionic polymer gate. The high responsivity from the visible to infrared regime (1.1 × 104 A/W at 635 nm and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Yoo et al demonstrated the efficient doping of Gr with polyethyleneimine (PEI) solution, which helps to increase the barrier height up to 0.26 eV and reduce the dark current by four orders of magnitude 45 . Figure 4b shows the electrostatic doping of a Gr/silicon-on-insulator PD by an ionic-polymer gate 47 . Ionic polymers are newly emergent dielectric media that help to improve the switching speed of Gr-based PDs.…”
Section: Gr/si Schottky Photodetectormentioning
confidence: 99%
“…Yoo et al demonstrated the efficient doping of Gr with polyethyleneimine (PEI) solution, which helps to increase the barrier height up to 0.26 eV and reduce the dark current by four orders of magnitude 45 . Figure 4b shows the electrostatic doping of a Gr/silicon-on-insulator PD by an ionic-polymer gate 47 . Ionic polymers are newly emergent dielectric media that help to improve the switching speed of Gr-based PDs.…”
Section: Gr/si Schottky Photodetectormentioning
confidence: 99%